Viscosity modeling in polyvinylpyrrolidone/chitosan blend for adhesive membrane processing (Research, Society and Development, 2021)
Polyvinylpyrrolidone and chitosan biopolymers are biomaterials used in wound treatment, due to their biological, physicochemical, and other properties, in addition to their processability. Controlling the viscosity of polymers is of fundamental importance for processing and consequently for the properties of membranes, such as adhesiveness, crucial for medical applications in wounds. In this sense, the research proposal was to simulate and evaluate the viscosity of polymeric mixtures of medium molar mass (QM) chitosan and polyvinylpyrrolidone (PVP) in different concentrations and proportions for the synthesis of adhesive membranes. To this end, the viscosity of pure polymers was evaluated in the literature, a linear model for the viscosity of the mixtures was simulated and, subsequently, the response surface methodology (MSR) was applied using the central composite model, for three QM/PVP ratios at different concentrations of the solutions. The viscosity of QM and PVP polymers present an exponential growth trend line, based on literature data, having a satisfactory regression coefficient, and the linear simulation model for viscosity of the mixtures, proved to be satisfactory, considering a variation of 5%. The surface response and contour graphs make evident the effect of solution concentration and polymer mix ratio, and in which mixing situations it is possible to achieve higher and lower viscosity levels. The information obtained in the research is extremely useful, aiding in the development of polymeric mixtures, in order to seek the best conditions, reduce the time of experiments focusing on points of interest.